2013
DOI: 10.3389/fnhum.2013.00063
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine-Induced Global Reductions in Resting-State BOLD Connectivity Reflect Widespread Decreases in MEG Connectivity

Abstract: In resting-state functional magnetic resonance imaging (fMRI), the temporal correlation between spontaneous fluctuations of the blood oxygenation level dependent (BOLD) signal from different brain regions is used to assess functional connectivity. However, because the BOLD signal is an indirect measure of neuronal activity, its complex hemodynamic nature can complicate the interpretation of differences in connectivity that are observed across conditions or subjects. For example, prior studies have shown that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 86 publications
4
30
1
Order By: Relevance
“…Subsequently, the WM-load related an increase in functional connectivity after caffeine intake observed here cannot be attributed to a nonspecific effect of this substance. Interestingly, a recent study combined fMRI and magnetoencephalography (MEG) to assess whether changes in resting state fMRI functional connectivity are due to vascular or neural factors (Tal et al, 2013). The functional connectivity changes in fMRI were paralleled by changes in MEG, which directly assesses neuro-electric activity.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the WM-load related an increase in functional connectivity after caffeine intake observed here cannot be attributed to a nonspecific effect of this substance. Interestingly, a recent study combined fMRI and magnetoencephalography (MEG) to assess whether changes in resting state fMRI functional connectivity are due to vascular or neural factors (Tal et al, 2013). The functional connectivity changes in fMRI were paralleled by changes in MEG, which directly assesses neuro-electric activity.…”
Section: Discussionmentioning
confidence: 99%
“…Each state of vigilance has specific characteristics that contribute to differences in spectral power (Niedermeyer et al , 1987, Cantero et al , 1999 and functional connectivity (Kuhnert et al , 2010. Several factors have been identified that influence state of vigilance: circadian rhythm (Kuhnert et al , 2010), task performance before the recording , including neuropsychological testing, medication use, or even caffeine intake (Siepmann et al , 2002, Barry et al , 2011, Tal et al , 2013. Body posture and recording environment may also affect vigilance and, consequently, functional connectivity measures.…”
Section: State Of Vigilancementioning
confidence: 99%
“…This type of research is still at an early stage with regard to robust replication, but preliminary indications are that there may be differences in response patterns following acute challenge between drugs as diverse as THC 130 , ketamine 131 , caffeine 132,133 , morphine and alcohol 134 and nicotine 135 . The latter drug increases connectivity within limbic circuits 136 .…”
Section: Acute Drug Intoxicationmentioning
confidence: 99%